2006
DOI: 10.1002/jmri.20696
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopy: Predicting long‐term neuropsychological outcome following pediatric TBI

Abstract: Purpose: To identify useful acute indicators of long-term neurocognitive outcome beyond clinical variables for children and adolescents treated for a traumatic brain injury (TBI). Materials and Methods:The efficacy of magnetic resonance spectroscopy (MRS) acquired 6 Ϯ 4 days after TBI in 20 children/adolescents in predicting intellectual and neuropsychological functioning one to four years post injury was assessed. Short echo-time single voxel MRS (SVS) from normal-appearing brain was compared to intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 43 publications
3
64
1
Order By: Relevance
“…80 In pediatric patients with accidental and nonaccidental TBI, MR spectroscopy has shown potential for providing early prognostic information regarding clinical outcomes. 62, [87][88][89][90][91][92][93][94] Reduced NAA has been correlated with impaired long-term neuropsychological function in children. 89,90,92,94 Elevated total Cho has also been described and may be related to diffuse axonal injury and/or repair.…”
Section: Mr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…80 In pediatric patients with accidental and nonaccidental TBI, MR spectroscopy has shown potential for providing early prognostic information regarding clinical outcomes. 62, [87][88][89][90][91][92][93][94] Reduced NAA has been correlated with impaired long-term neuropsychological function in children. 89,90,92,94 Elevated total Cho has also been described and may be related to diffuse axonal injury and/or repair.…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…62, [87][88][89][90][91][92][93][94] Reduced NAA has been correlated with impaired long-term neuropsychological function in children. 89,90,92,94 Elevated total Cho has also been described and may be related to diffuse axonal injury and/or repair. 84,95 Studies have shown that elevated lactate levels are more common following nonaccidental TBI 62,87 and are strongly correlated with poor outcomes.…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…MRS provides a sensitive assessment of post-injury neurometabolite alterations, particularly in tissue with no visible injury on conventional imaging, and has shown potential for providing early prognostic information regarding clinical outcome in pediatric patients with accidental and nonaccidental TBI (Aaen et al, 2010;Ashwal et al, 2000;Babikian et al, 2006;Brenner et al, 2003;Holshouser et al, 1997Holshouser et al, , 2005 Studies using proton MRS in children have found similar neurometabolite alterations after injury. Typically, N-acetyl aspartate (NAA), an amino acid synthesized in mitochondria, is a neuronal and axonal marker that is reduced as a result of neuronal loss or dysfunction after injury.…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…Most of the research by the same group focuses on the acute (approximately 1 week post-injury) metabolic changes following injury and the possibility that MRS offers early prognostic information regarding outcome (Ashwal et al, 2000;Babikian et al, 2006;Brenner et al, 2003;Holshouser et al, 2005). These investigators have found reductions of NAA/Cr or NAA/Cho and increases of Cho/Cr in normal appearing occipital gray matter and parietal white matter (Ashwal et al, 2000;Babikian et al, 2006;Brenner et al, 2003;Holshouser et al, 2005). Because Cr has been thought to remain constant, Cr has often been used in the denominator in computing metabolite ratios and not studied independently (Ashwal et al, 2006a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Because Cr has been thought to remain constant, Cr has often been used in the denominator in computing metabolite ratios and not studied independently (Ashwal et al, 2006a,b). Researchers have shown correlations between reduced NAA/Cr and NAA/Cho and increased Cho/Cr and severity of injury as assessed by admission GCS score (Ashwal et al, 2000;Brenner et al, 2003), as well as by longer-term neurological (Ashwal et al, 2000;Brenner et al, 2003) and neuropsychological (Babikian et al, 2006;Brenner et al, 2003) outcomes.…”
Section: Introductionmentioning
confidence: 99%